RELATIONSHIPS BETWEEN SOIL ORGANIC CARBON STORAGE AND INUNDATION DYNAMICS IN HEADWATER FLOODPLAINS - Papac, Mariah E., author; Morrison, Ryan R., advisor; White, Daniel, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2026)
Floodplains serve as carbon storage hotspots where periodic inundation supportsvegetation growth, nutrient-rich sediment deposition, and organic matter accumulation. Headwater floodplains, in particular, store substantial amounts of soil organic carbon (SOC) relative to their watershed area. However, the relationship between inundation dynamics (e.g., inundation frequency) and floodplain SOC content remains poorly understood. I hypothesized that SOC accumulation would follow a non-linear response to floodplain inundation, with intermediate inundation recurrence intervals yielding the highest carbon storage. To test this hypothesis, I collected floodplain soil cores from three headwater rivers in the Colorado Rockies: Little Beaver Creek, Lower Elkhorn Creek, and the Laramie River. All three floodplain reaches were slated for restoration to improve lateral connectivity with the floodplain. The coring locations were randomly chosen based on pre-selected surface elevation bins relative to the channel. I processed the floodplain samples, which included organic layer and mineral samples. I calculated each mineral sample’s bulk density and measured its carbon content using an elemental analyzer. I then created two-dimensional steady-state hydrodynamic models for each floodplain reach and simulated the 2-, 5-, 10-, 25-, 50-, 100-, 200-, and 500-yr recurrence interval discharges. I grouped cores based on their initial inundation discharge to determine whether frequency of inundation (i.e., cores flooded in the 2-yr recurrence interval discharge experienced the most frequent inundation) affected SOC storage. I found surface elevation relative to the channel to be a weak predictor of SOC content and floodplain SOC stocks to be smaller than, but of comparable magnitude to, other Colorado headwater floodplains. For the relationship between SOC and inundation frequency, I found a bimodal distribution for Lower Elkhorn Creek and Laramie River, with the largest peak occurring for cores located in infrequently inundated areas (200- and 500-yr inundation) and the second peak occurring in frequently inundated areas (2- and 5-yr). Little Beaver Creek did not show the bimodal distribution due to a lack of cores located within the 2-, 5-, and 25-yr recurrence interval inundated areas. The bimodal results align with the few studies completed thus far to determine the relationship between inundation frequency and floodplain SOC. These studies were conducted on climatically different floodplains, but for the four floodplains studied, a single inundation regime, infrequent or frequent, corresponded with the greatest SOC storage. The conflicting results suggest that multiple processes may influence SOC storage with varying importance, depending on the floodplain. The disagreement between floodplains underscores the complex processes occurring in these systems and the importance of site-specific data collection to determine the efficacy of restoration if carbon sequestration is the goal.
Keywords: Headwater streams; Inundation Frequency; Floodplains; Soil Organic Carbon; Hydraulic Modeling